ANALISIS PERTANGGUNGJAWABAN KEUANGAN ORGANISASI NIRLABA DAN PENYUSUNAN LAPORAN KEUANGAN SESUAI DENGAN PSAK 45 DI MASJID AL-MUTTAQIN BEKASI - Yayang Novita Sari; Hayuningtyas Pramesti Dewi (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2018)
This research raises the issue of financial accountability for non-profit organizations. The object of the research was conducted at Al Muttaqin Mosque Jatibening Bekasi for the 2016-2017 reporting year. Data obtained from cash in and out cash recap, observation and interview. The results of the study were that the Al Muttaqin Mosque had not made a Financial Report in accordance with PSAK 45 so that the preparation of the Financial Statements in accordance with PSAK 45 was tried to be compiled in the study.